Analysis of Customer Experience on Revisit Intention - Nazarudin, Hamzah; Nino , Indawati (Public Policy, 2025)
The purpose of this study is to investigate the impact of customer experience, which includes, education, aesthetics, entertainment, and escapism on the intention of tourists to revisit attractions in Lembata Regency. The study involved 100 tourists who had visited local attractions at least twice. A purposive sampling technique was used, focusing on tourists over 20 years of age. Multiple linear regression was applied for data analysis. Results show that customer experiences, including educational, aesthetic, entertainment, and escapism values, have a significant, positive influence on the intention to revisit. The study found that 57.3% of revisit intentions could be explained by these customer experiences.